Multistate occupancy modeling improves understanding of amphibian breeding dynamics in the Greater Yellowstone Area. Issue 1 (2nd January 2019) - Gould, William R.; Ray, Andrew M.; Bailey, Larissa L.; Thoma, David; Daley, Rob; Legg, Kristin
Abstract: Discerning the determinants of species occurrence across landscapes is fundamental to their conservation and management. In spatially and climatologically complex landscapes, explaining the dynamics of occurrence can lead to improved understanding of short‐ vs. long‐term trends and offer novel insight on local vs. regional change. We examined the changes in occupancy for two species of anurans with different life histories over a decade using hundreds of wetland sites in Yellowstone and Grand Teton National Parks. To account for the joint dynamics of wetland drying and amphibian breeding, we adopted a multistate occupancy model as a means to investigate mechanistic relationships of observed occurrence patterns with climatological drivers of wetland hydrologic variability. This approach allowed us to decompose occupancy dynamics into habitat changes caused by wetland drying and amphibian breeding activity, conditional on available water and previous breeding state. Over our 10‐yr time series, we observed considerable variability in climate drivers and the proportion of dry wetlands. Boreal chorus frogs ( Pseudacris maculata ) were more responsive to changes in wetland inundation status than Columbia spotted frogs ( Rana luteiventris ), as indicated by higher breeding colonization probabilities under favorable (wet) conditions. Both species had high probabilities of breeding persistence in permanently inundated wetlands with prior breeding. Despite the absence of multi‐year drought in our time series, mechanistic relationships described here offer insights on how future climate variation may result in reduced and/or shifted occurrence patterns for pond‐breeding anurans in the Greater Yellowstone Area. Further, our modeling approach may prove valuable in evaluating determinants of occurrence for other species that are dependent on wetlands or other dynamic habitats.